Prospects for the development of prosumer energy in Poland - Magdalena Zajaczkowska (Institute of Economic Research (IER), 2015)
Renewable energy will play a key role in the transition towards a competitive, secure and sustainable energy system. In 2014 the Commission proposed an objective to increase the share of renewable energy to at least 27% of the EU's energy consumption by 2030. The European Council endorsed this target which is binding at EU level. The Renewable Energy Directive (Directive 2009/28/EC of the European Parliament and of the Council of 23 April 2009 on the promotion of the use of energy from renewable sources and amending and subsequently repealing Directives 2001/77/EC and 2003/30/EC) was implemented in Poland on 20 February 2015 by the new renewable energy sources act. The objective of this article is to analyse the current state of the Polish energy sector related to the prosumer energy industry. It also describes the future potential for the development of prosumer energy in Poland. The analysis was conducted in the light of the new EU climate and energy initiatives. At the beginning, the article presents the current general state in EU's energy sector. European Union Climate and Energy Package targets up to 2050 and the state of renewable energy use gives the background to conduct an analysis of prospects for the development of prosumer energy in Poland. That is why the last part is devoted to the prosumer energy sector in Poland in the context of European Union regulations. The critical analysis of the current situation in that sector has made it possible to evaluate prospects for the development of prosumer energy in Poland in the context of the recently introduced legal regulations.
Keywords: A11; E61; F50; H89; 330; prosumer; energy sources; renewable sources of energy; climate and energy policies